Caracterização da performance de cultivares de feijão-comum em três épocas de semeadura em Goiás, por modelo de simulação - Justino, Ludmilla Ferreira (2020)
Common bean (Phaseolus vulgaris L.) is one of the most produced and consumed legume species in the world, which is of great importance in the social and economic sphere. Due to its great adaptive capacity, common bean can be produced in different seasons, cultivation systems and edaphoclimatic conditions, which favors the greater exploitation of the crop throughout the national territory, resulting in a wide variability of bean types, groups and cultivars. Due to its genetic characteristics, each cultivar responds differently to environmental variables, different soil and management, and these characteristics can be studied through computational models that simulate the growth, development and yield of the cultures. The aim of this work was to characterize the performance of four commercial cultivars of common bean “in silico”, in addition to parameterize and validate the CROPGRO-Drybean model, comparing the phenotypic characteristics of the cultivars and evaluating their performance in the three planting seasons and different sowing dates in the bean production areas of Goiás State. The CROPGRODrybean model was parameterized and validated for the cultivars Pérola, BRS Estilo, BRS Esplendor and IPR Uirapuru by genetic algorithm using field experiments from the dry bean breeding program. Subsequently, the yields of common bean cultivars were simulated in the producing regions of Goiás State, during the wet, dry and winter seasons, in several sowing dates and a cluster analysis was performed to define homogeneous environmental groups. The environmental variability regarding the locations and dates used in the validation were captured by the CROPGRO-Drybean model and the parameterized coefficients of the four cultivars are more suitable for simulations in the winter season. Earlier sowing dates provided higher yields during wet and dry seasons. The factors that most affected the clusters in the wet and dry seasons were cultivar and sowing date, while in winter they were municipality and cultivar.